2020
DOI: 10.1016/j.jval.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Use of Surrogate Measures in Pivotal Trials and Health Technology Assessment Decisions: A Retrospective Analysis of NICE and CADTH Reviews of Cancer Drugs

Abstract: Methods: Cancer drug approvals from 2012 to 2016 were categorized by demonstrating benefit on overall survival (OS), progression-free survival, disease response, or having no comparator. Approvals were analyzed by benefit category and health technology assessment recommendation. The association between benefit (surrogate vs OS) and recommending a drug was examined using descriptive statistics and linear probability models controlling for unmet need, orphan designation, and costeffectiveness.Results: Of 42 canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…A prior review of regulatory submissions found that only 9% (4/43) of non-RCT submissions used an adjusted ITC. 23 In this analysis, the first case of adjusted ITC was not until 2015 (3, 7% of 2015 submissions) increasing to 29% (30) in 2019. Over the same period, use of naive ITC reduced as a proportion of all submissions between 2015 (22, 48%) and 2019 (22, 22%).…”
Section: Methodological Approaches For Ecsmentioning
confidence: 78%
See 2 more Smart Citations
“…A prior review of regulatory submissions found that only 9% (4/43) of non-RCT submissions used an adjusted ITC. 23 In this analysis, the first case of adjusted ITC was not until 2015 (3, 7% of 2015 submissions) increasing to 29% (30) in 2019. Over the same period, use of naive ITC reduced as a proportion of all submissions between 2015 (22, 48%) and 2019 (22, 22%).…”
Section: Methodological Approaches For Ecsmentioning
confidence: 78%
“…The increasing availability of RWD and gradual acceptance by HTA and regulatory bodies has been extensively covered by other commentators. 23,[31][32][33][34] In relation to SAT-based submissions, RWD ECs may be considered more appropriate as they allow more relevant comparator cohorts to be constructed and enable the collection of more contemporary standard of care treatments than prior clinical trials data. However, we suggest that manufacturers assess other important factors when designing an EC as there is variation between HTA bodies in acceptance of RWD.…”
Section: Impact Of Ecs On Hta Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Four previous studies have investigated the impact of surrogate endpoints on HTA decisions. Two studies focused on cancer drugs, 8,9 and 2 considered the range of technology appraisals undertaken by either the National Institute of Health and Care Excellence (NICE) in the United Kingdom or the Canadian Common Drug Review. 10,11 However, these previous studies did not assess HTA agencies' approach to validation of the surrogate endpoints or how this related to their coverage recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…While NICE and ICER represent two of the largest and most consequential HTA agencies, we know very little about how their methodologies compare or the degree to which they reach similar conclusions. Studies by Chabot and Rocchi in 2014 [6], and Pinto and colleagues in 2020 compared English and Canadian HTA for oncology drugs [7] and both studies found variation in recommendations due to differences in available policy tools to address issues of clinical uncertainty and unfavorable cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%